Electromagnetic ion cyclotron waves in the Earth's magnetosphere with a kappa‐Maxwellian particle distribution. Issue 10 (9th October 2015) - Sugiyama, Hajime; Singh, Satyavir; Omura, Yoshiharu; Shoji, Masafumi; Nunn, David; Summers, Danny
Abstract: A theoretical model to study electromagnetic ion cyclotron (EMIC) waves in kappa‐Maxwellian plasma is developed. The plasma is assumed to have five components, i.e., electrons, cool and hot protons, and singly charged helium and oxygen ions. The kappa‐Maxwellian anisotropic particle distribution function is assumed for the hot protons. We use the Kyoto University Plasma Dispersion Analysis Package, a full dispersion solver developed at Kyoto University, to obtain the numerical results and delineate the oxygen, helium, and proton bands. Higher harmonics of the EMIC waves are also studied, and the effects of the kappa distribution on the growth of these waves are clearly demonstrated. Our results are applied to Cluster spacecraft observations of EMIC waves in the inner magnetosphere. Key Points: EMIC wave instabilities in a kappa‐Maxwellian are studied Characteristics of higher harmonics of EMIC waves are identified Technical description of KUPDAP dispersion solver is given